2010
DOI: 10.2478/v10018-010-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Sea Level Variations in the Eastern Tropical Pacific

Abstract: ABSTRACT. The objective of this paper is to provide an insightful interpretation for the non-linearity of the inter-annual signal in sea level change in the eastern tropical Pacific. Such a non-linearity has been already discussed elsewhere for global ocean. Herein, the residual sea level anomaly time series from TOPEX/Poseidon and Jason-1 altimetry is obtained by removing the significant deterministic signals from the original sea level anomaly data. Since the eastern tropical Pacific is a profound region whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Our study supplements the predictive analysis by Niedzielski and Kosek (2009) in the sense that it shows that low-order ARMA methods can have dissimilar performance in modelling irregular sea level fluctuations in the eastern tropical Pacific. This is also in agreement with what has been envisaged by Niedzielski (2010) who assumed linear processes to serve well the purpose of irregular sea level modelling at some sites located off the Equator in the eastern equatorial Pacific.…”
Section: Resultssupporting
confidence: 79%
“…Our study supplements the predictive analysis by Niedzielski and Kosek (2009) in the sense that it shows that low-order ARMA methods can have dissimilar performance in modelling irregular sea level fluctuations in the eastern tropical Pacific. This is also in agreement with what has been envisaged by Niedzielski (2010) who assumed linear processes to serve well the purpose of irregular sea level modelling at some sites located off the Equator in the eastern equatorial Pacific.…”
Section: Resultssupporting
confidence: 79%
“…Journal of Geophysical Research: Oceans of SLA implies the considerable nonlinearity in its dynamics, which adds to uncertainties and difficulties of sea level prediction in the WTP (Niedzielski, 2010;Niedzielski & Kosek, 2010). On the other hand, SLAs are dynamically associated with the thermocline displacements and the upper ocean geostrophic current anomalies.…”
Section: 1029/2020jc016616mentioning
confidence: 99%
“…Statistical analysis of previous studies (Burgers & Stephenson, 1999; Niedzielski, 2010; Niedzielski & Kosek, 2010) suggested that SLAs over the tropical Pacific, resembling sea surface temperature (SST) anomalies, do not strictly conform to the normal distribution. As shown in Figure 1d, the prevailing negative skewness values in the WTP are probably linked to the predominance of El Niño over La Niña in their SLA signatures (Niedzielski & Kosek, 2010), which may be related with not only the ENSO's asymmetry but also the nonlinearity in ocean response to ENSO (An & Kim, 2017; Guan et al, 2019; Im et al, 2015; Niedzielski & Kosek, 2010; Świerczyńska et al, 2014; Wen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stochastic low-order autoregressive moving average (ARMA) and generalized autoregressive conditional heteroscedastic (GARCH) models were used to model irregular sea level fluctuations in the least-squares residuals of the sea level anomaly data (Niedzielski and Kosek, 2011b). The authors found that AR and ARMA models are adequate, with a successful fit to these residuals in some patchy bits of the equatorial Pacific.…”
Section: Sea Level Changementioning
confidence: 99%